Incidence, predictors and clinical outcomes of residual stenosis after aortic valve-in-valve - Bleiziffer, Sabine; Bekeredjian, Raffi (Heart, 2018)
Objective We aimed to analyse the incidence of prosthesis–patient mismatch (PPM) and elevated gradients after aortic valve in valve (ViV), and to evaluate predictors and associations with clinical outcomes of this adverse event. - Methods A total of 910 aortic ViV patients were investigated. Elevated residual gradients were defined as ≥20 mm Hg. PPM was identified based on the indexed effective orifice area (EOA), measured by echocardiography, and patient body mass index (BMI). Moderate and severe PPM (cases) were defined by European Association of Cardiovascular Imaging (EACVI) criteria and compared with patients without PPM (controls). - Results Moderate or greater PPM was found in 61% of the patients, and severe in 24.6%. Elevated residual gradients were found in 27.9%. Independent risk factors for the occurrence of lower indexed EOA and therefore severe PPM were higher gradients of the failed bioprosthesis at baseline (unstandardised beta −0.023; 95% CI −0.032 to –0.014; P<0.001), a stented (vs a stentless) surgical bioprosthesis (unstandardised beta −0.11; 95% CI −0.161 to –0.071; P<0.001), higher BMI (unstandardised beta −0.01; 95% CI −0.013 to –0.007; P<0.001) and implantation of a SAPIEN/SAPIEN XT/SAPIEN 3 transcatheter device (unstandardised beta −0.064; 95% CI −0.095 to –0.032; P<0.001). Neither severe PPM nor elevated gradients had an association with VARC II-defined outcomes or 1-year survival (90.9% severe vs 91.5% moderate vs 89.3% none, P=0.44). - Conclusions Severe PPM and elevated gradients after aortic ViV are very common but were not associated with short-term survival and clinical outcomes. The long-term effect of poor post-ViV haemodynamics on clinical outcomes requires further evaluation.
Gesehen am 11.10.2019